2004
DOI: 10.1007/s00192-004-1202-4
|View full text |Cite
|
Sign up to set email alerts
|

Do subjective symptoms of obstructive voiding correlate with post-void residual urine volume in women?

Abstract: The objective was to determine if symptoms of obstructive voiding correlate with post-void residual urine volume measured by catheterization. A cross-sectional study of 134 consecutive women referred to a tertiary urogynecology clinic was performed. Subjects were interviewed regarding three types of obstructive voiding symptoms: a sensation of incomplete emptying, straining to void, and slow urine stream. Post-void residual urine volume was measured by catheterization as the gold standard. Data for each sympto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 19 publications
(16 reference statements)
1
10
0
Order By: Relevance
“…Although obstructive voiding symptoms were commonly reported in this population, these symptoms did not reflect the actual rates of urinary retention. Our data is consistent with previous investigators who also found a poor correlation between obstructive voiding symptoms and urinary retention in women [8,9]. Before this study, we hypothesized that women with higher PVR will have more prominent obstructive symptoms; therefore, we arbitrarily chose the volume of 150 ml rather than 100 ml as the cutoff for urinary retention.…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…Although obstructive voiding symptoms were commonly reported in this population, these symptoms did not reflect the actual rates of urinary retention. Our data is consistent with previous investigators who also found a poor correlation between obstructive voiding symptoms and urinary retention in women [8,9]. Before this study, we hypothesized that women with higher PVR will have more prominent obstructive symptoms; therefore, we arbitrarily chose the volume of 150 ml rather than 100 ml as the cutoff for urinary retention.…”
Section: Discussionsupporting
confidence: 77%
“…Unfortunately, the relationship between symptoms of obstructive voiding in women and elevated PVR and bladder outlet obstruction is unclear. Previous studies present conflicting results when investigating the utility of different subjective measures of voiding dysfunction as they relate to patients' objective symptoms [2,[5][6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…Our group included all women seeking care in a female pelvic medicine clinic and not only those women with urge or mixed incontinence. Recently, Al-Shahrani and Lovatsis [8] reported on the predictive value of obstructive voiding symptoms and showed a poor relationship between symptoms of incomplete emptying, straining, and poor flow in a group of 134 women presenting to their Urogynecology unit. Our data support this lack of relationship; however, the symptom of splinting to void, which was significant on our univariate analysis, was not assessed in these patients.…”
Section: Discussionmentioning
confidence: 99%
“…The presence of exaggerated urethral or urethrovesical junction angulation with a high, fixed urethra located in the retro pubic area is suggestive of urethral hypercorrection [57]. Although there is no established cutoff between normal and abnormal PVR, and no evidence of correlation between PVR and symptoms of obstructive voiding, PVR of more than 100 ml is considered abnormal in women [58-60]. Blaivas and Groutz proposed an obstruction nomogram for women on the basis of free maximal flow rate and maximal detrusor pressure during pressure-flow study [61].…”
Section: Evaluation and Management Of Voiding Dysfunction After Mid-umentioning
confidence: 99%